2014
DOI: 10.1186/1471-2393-14-310
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of birth outcomes in rural Sarlahi District, Nepal: a population-based prospective cohort

Abstract: BackgroundWhile seasonality of birth outcomes has been documented in a variety of settings, data from rural South Asia are lacking. We report a descriptive study of the seasonality of prematurity, low birth weight, small for gestational age, neonatal deaths, and stillbirths in the plains of Nepal.MethodsUsing data collected prospectively during a randomized controlled trial of neonatal skin and umbilical cord cleansing with chlorhexidine, we analyzed a cohort of 23,662 babies born between September 2002 and Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
2
21
1
1
Order By: Relevance
“…Data from Nepal showed that the highest preterm birthing corresponded to high temperature exposures [37], possibly due to greater risk of labour induction as a result of decreased uterine blood flow when dehydration sets in [38]. On the other hand, the low birthing during the dry season can be attributed to increased risk of infection such as malaria during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Nepal showed that the highest preterm birthing corresponded to high temperature exposures [37], possibly due to greater risk of labour induction as a result of decreased uterine blood flow when dehydration sets in [38]. On the other hand, the low birthing during the dry season can be attributed to increased risk of infection such as malaria during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…Lawlor et al (2005) reported that the birth weight was seasonally patterned in Aberdeen, Scotland, with LBWs among those born in the winter months and highest birth weights among those born in the autumn months. A similar study has reported that newborn born in the fall had a significantly lower birth weight than those born in the winter (Onyiriuka 2006;Chodick et al 2007;Strand et al 2012;Hughes et al 2014;Zhang et al 2017), indices that the extremes of temperature may be an important determinant of LBW. Onyiriuka (2006) has reported that the mean birth weights significantly differed between wet and dry seasons in newborns born in Nigeria (p<0.01).…”
Section: Discussionmentioning
confidence: 81%
“…The analysis of seasonal variations in birth weights may enable researchers to suggest specific factors that influence the measure of LBW (McGrath et al 2005;Chodick et al 2007;Hughes et al 2014;Lei et al 2016;Zhang et al 2017). Maternal exposure to the lower outdoor ambient temperature in mid-trimesters can also lead to an increase in LBW (Strand et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the observed incidences of LBW and PTB in this cohort were slightly lower than previous estimates in the region, reflecting an overall improvement in health in the population. Among all women enrolled, 25% gave birth to an LBW infant, compared with 30.4% in previous studies; 13% gave birth preterm, compared with 18.3% in previous studies (15,39). In the parent trial of maternal influenza immunization, influenza vaccination during pregnancy was effective in prevention of influenza infection in infants and was also associated with increased birthweight (20).…”
Section: Discussionmentioning
confidence: 90%